2013
DOI: 10.4236/ijg.2013.48113
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Near-Surface Air Temperature and Precipitation Using WRF with 5-km Resolution in the Northern Patagonia Icefield: A Pilot Simulation

Abstract: The regional Weather and Research Forecast (WRF) Model was run for the 2000-2010 period over the Northern Patagonia Icefield (NPI) with an horizontal resolution of 5 km. The regional model was initialized using the NCEP/NCAR atmospheric Reanalysis database. The simulation results, centered over the NPI, were validated against the observed data from the local surface stations in order to evaluate the improvement of the model results due to its increased horizontal resolution with respect to the lower resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Fewer studies compare a 10-km domain with a higher-resolution grid that is explicitly resolving convection. Villarroel et al (2013) found that a high-resolution 5-km domain over southern Chile improved model performance for both temperature and precipitation relative to the driving data, and this result was attributed to improved topographical resolution, but the domain was not compared with a lower-resolution WRF grid. In a simulation over central Japan, Kusaka et al (2010) found that 4-km resolution represented a 5-yr climatology well; again, these results were compared with a lower-resolution WRF grid.…”
Section: Discussionmentioning
confidence: 96%
“…Fewer studies compare a 10-km domain with a higher-resolution grid that is explicitly resolving convection. Villarroel et al (2013) found that a high-resolution 5-km domain over southern Chile improved model performance for both temperature and precipitation relative to the driving data, and this result was attributed to improved topographical resolution, but the domain was not compared with a lower-resolution WRF grid. In a simulation over central Japan, Kusaka et al (2010) found that 4-km resolution represented a 5-yr climatology well; again, these results were compared with a lower-resolution WRF grid.…”
Section: Discussionmentioning
confidence: 96%
“…Evaluating the simulated amounts of precipitation remains challenging in the absence of reliable observations, but, qualitatively, RACMO2 is able to resolve the sharp zonal climate gradients, and the modeled high snowfall on the ice fields is broadly confirmed by firn cores. Moreover, equivalent amounts were simulated by the Weather Research and Forecasting (WRF) model at the same horizontal resolution on the NPI (Schaefer et al 2013;Villarroel et al 2013), with very similar spatial patterns. Using a linear precipitation model, highresolution terrain information, and observed oxygen isotope ratios, Smith and Evans (2007) predicted similarly high spatial variability in the region 448-468S, with strong dependency on the orientation of the local topography.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, to date there are no empirically-based studies of the meteorological conditions over both sides of the Patagonian Icefields that can constrain the mass balance modeling studies. Due to the lack of observationbased analyses, high uncertainties exist in the glacier surface mass balance model parameterizations precluding a complete validation of the simulated accumulation (Villarroel et al, 2013) as well as a robust assessment of the response of the glaciers to projected climate change.…”
Section: Introductionmentioning
confidence: 99%